Flavonoid and Phenolic Waru Leaf Extract (Hibiscus tiliaceus) and Antioxidant Activity - Lina Oktavia Rahayu; Oktavina Kartika Putri; Rizki Daniar Manggarani (State University of Malang or Universitas Negeri Malang (UM), 2022)
Waru leaf (Hibiscus tiliaceus) is plant that contains natural flavonoids and phenolic compounds and is useful as an antioxidant. Flavonoids and phenolics can be extracted optimally if using a suitable extraction solvents. This study aims to determine the total flavonoid, phenolic, and antioxidant levels of waru leaf extract using several extraction solvents. The total flavonoid content was tested using the AlCl3 colorimetric method, total phenolic content using the Folin-Ciocalteu method, and antioxidant levels using the DPPH method. The total flavonoid content of the extract with methanol, ethanol, and water solvents respectively 121,630 ± 2,014 gQE/g; 133,190 ± 1,434 gQE/g; 78.320 ± 1.799 gQE/g. The total phenolic content of the extract with methanol, ethanol, and water solvents were 9,151,480 ± 58,969 gGAE/g; 7,978,610 ± 84,845 gGAE/g; 4,789,690 ± 14,576 gGAE/g. Extract with methanol solvent has very weak antioxidant activity (IC50 = 710,680 ± 3,747 g/mL). Extract with ethanol solvent has very weak antioxidant activity (IC50 = 989.150 ± 0.798 g/mL). Extract with water solvent has very weak antioxidant activity (IC50 = 1,643,480 ± 1,828 g/mL). Ethanol extract had the highest total flavonoid content. Methanol extract had the highest total phenolic content and very weak antioxidant activity.